GAMBARAN KARAKTERISTIK APOTEKER DI PUSKESMAS WILAYAH BARAT, TENGAH, DAN TIMUR INDONESIA - Putra, Aditya Maulana Perdana; Sandi, Dita Ayulia Dwi; Sari, Okta Muthia; Intannia, Difa; Rizki, Muhammad Ikhwan; Rahmatullah, Satrio Wibowo; Lingga, Herningtyas Nautika (Universitas Borneo Lestari, 2024)
In current global trends, pharmacy continues tobe a more clinical and patient-oriented profession, with greater responsibility and accountability for pharmaceutical services in the clinical environment. The participation of pharmacists is very important in the implementation of pharmaceutical services in accordance with the standards in the Community Health Centres. The study aims to describe the characteristics of pharmacists in the Community Health Centers of DKI Jakarta, South Kalimantan and South Sulawesi. This type of research is descriptive and observer-designed, conducted from June to August 2024 online in community health centres in DKI Jakarta, South Kalimantan and South Sulawesi. The data were collected by distributing online questionnaires through Googleforms, with the support of HISFARKESMAS. The collected data was processed descriptively by calculating the percentage of each feature. The characteristics of 359 pharmacists in the three regions (DKI Jakarta, South Kalimantan and South Sulawesi) were females (82.45%) and men (17.55%), with respondents aged 23-30 (32.87%), 31-40 (46.52%), 41-50 (18.38%) and 51-60 (2.23%). The most recent education in the pharmacist profession (93.87%) and in strata 2 (6.13%), the number of pharmacists in one health center is 58.22% with a pharmacist, 30.08% with two pharmacists and 11.70% more than two pharmacists. The duration of working as a pharmacist is 0-2 years, 3 to 5 years (27.02%), 6 to 10 years (16.16%) and more than 10 years (29.81%).